Alkylation of staurosporine to derive a kinase probe for fluorescence applications - Disney, Alexander J.M.; Kellam, Barrie; Dekker, Lodewijk V. (Wiley-VCH Verlag, 2016)
The natural product staurosporine is a high-affinity inhibitor of nearly all mammalian protein kinases.The labelling of staurosporine has proven effective as a means of generating protein kinase research tools. Most tools have been generated by acylation of the 4’-methylamine of the sugar moiety of staurosporine. Herein we describe the alkylation of this group as a first step to generate a fluorescently labelled staurosporine. Following alkylation, a polyethylene glycol linker was installed, allowing subsequent attachment of fluorescein. We report that this fluorescein–staurosporine conjugate binds to cAMP-dependent protein kinase in the nanomolar range. Furthermore, its binding can be antagonised with unmodified staurosporine as well as ATP, indicating it targets the ATP binding site in a similar fashion to native staurosporine. This reagent has potential application as a screening tool for protein kinases of interest.